Adenosine Deaminase (ADA) in Rheumatoid Arthritis in patients (RA) - Huda Th. Al-Marsomi (مجلة كلية الطب, 2009)
Background: Rheumatoid Arthritis (RA) is heterogenous syndrome. Because the diversity of disease processes and formation of complex lymphoid microstructures that indicate the multiple T cell activation pathways are involved .affected patients have major abnormalities in the T cell pool with clonally expanded CD4  + T cell that lose expression of the CD28null molecule and lack the ability for profiliration. Adenosine deaminase (ADA) is an indicator of the proliferation and differenation of lymphocyte, in particularly the T cell subcells. Patients and Methods: Total ADA levels were measured in the sera of RA patients and healthy group according to Giusti (1981). Results: The mean value of ADA was lower in patients with RA than control group with no significant differences. Conclusion: the lower value of ADA (which involved in the proliferation of lymphocyte) in RA patients may results from the predominance of CD4 + T cells in the peripheral blood